Educating Learners with SEND in One Private Mainstream School in Dubai: Effectiveness and Challenges of Policy Implementation - Badawieh, Muntaha (2023)
This study investigates the SEND policy implementation in one private school in Dubai. It highlights whether the school’s teachers and support staff adopted and effectively implemented the SEND inclusion policy. The investigation process focuses on three areas which are curriculum modifications, Assessment differentia tion, and teacher’s professional development. A qualitative research study of semi structured interviews has been conducted to investigate the effectiveness and chal lenges of SEND policy implementation; for this purpose, interviews were conducted with the school’s teachers for data analysis; the researcher has decided to use the qualitative approach because it shows a subjective evaluation of beliefs, behaviour, and attitudes, the total number of participants were two subject teachers and one school principal. This study investigated all the significant aspects, and the overall result was conducted to provide the proper recommendations. The qualitative study findings indicate that the school policy implementation is very effective, and teachers’ awareness of the inclusion policy is appropriate. Nevertheless, they face difficulties in accommodating students’ needs in the classroom due to the massive number of students in each classroom. Also, it showed that the inclusion support team acts as a backbone in supporting the teachers through the weekly meetings, which help them modify the curriculum and accommodate the assessment for their students. In terms of challenges, the school has few numbers of inclusion support teachers; therefore, it leads to some challenges teachers face when implementing the policy.